130k views
4 votes
Substitution algebra

Please answer fast :) Don't answer this with troll stuff plz, I don't have much points ​

Substitution algebra Please answer fast :) Don't answer this with troll stuff plz-example-1
User EstebanLM
by
5.0k points

1 Answer

3 votes

Answer:

We will use substitution to solve the system. Step 1 is partially complete.


y = -2x - 9\\6x - 5y = -19\\\\6x - 5(-2x - 9) = -19\\\\6x + 10x + 45 = -19\\\\16x + 45 = -19\\\\16x = -64\\\\x = -4

We will now use what we got for x to solve for y in one of the original equations.


6(-4) - 5y = -19\\\\-24 - 5y = -19\\\\-5y = 5\\\\y = -1

The solution is (-4, -1).

User Punit Sharma
by
5.6k points